Assessment of photocatalytic potentiality and determination of ecotoxicity (using plant model for better environmental applicability) of synthesized copper, copper oxide and copper-doped zinc oxide nanoparticles. - Debadrito Das; Animesh Kumar Datta; Divya Vishambhar Kumbhakar; Bapi Ghosh; Ankita Pramanik; Sudha Gupta; Aninda Mandal (PLoS ONE)
Nps synthesis, characterization and azo-dye degradation A facile cost effective wet chemical method of synthesis is proposed for Cu-NPs, CuO-NPs and Cu-doped ZnO-NPs. The nanomaterials are opto-physically characterized for nano standard quality. Cu-doped ZnO-NPs based catalytic system is found to possess most efficient photocatalytic activity in degradation of two organic azo-dyes namely methyl red (MR) and malachite green (MG) that are released as industrial effluents in eco-environment intercollegium. Two possible photocatalytic degradation pathways are proposed to understand the mechanism of interaction prevailing during the mineralization of MR and MG dyes. Such study provides insight for waste water management. The uniqueness of the present work is 1) possible routes of MG dye degradation by Cu-doped ZnO-NPs and subsequent intermediate by-products are novel and pioneered of its kind. 2) two new intermediate byproducts are identified suggesting prevalence of multiple MR degradation pathways by Cu-doped ZnO-NPs. Assessment of ecotoxicity For assessment of residual NPs impact on environment, eco-toxicological assay is performed using plant system (Sesamum indicum L.) as model. The study encompasses seed germination, seedling morphology, quantification of endogenous H2O2 and MDA generation, estimation of DNA double strand break and analysis of cell cycle inhibition. Results highlight reduced ecotoxicity of Cu-doped ZnO-NPs compared to the other synthesized nanomaterials thereby suggesting better environmental applicability in waste water purification.